ORGANIZATION OF TEACHING FUTURE PHILOLOGISTS DISCUSSION IN ENGLISH BASED ON PROBLEMATIC SITUATIONS - Ірина Зайцева (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article deals with the peculiarities of organizing future philologists' discussion in English in the process of teaching on the basis of problematic situations.  Such notions as "discussion", "problematic situation", "mind map", "communicative-discussion skills" are defined and stages of teaching discussion with its peculiarities are analysed. The methodical recommendations for choosing educational materials for teaching students discussion in English based on problematic situations have been given. The examples of the exercises are presented and demands for articles' and video records' selection and their advantages are pointed out.